Life-threatening electrolyte abnormalities in pyloric stenosis - Christopher Jacobs; Kevin Johnson; Faraz A. Khan; Moiz M. Mustafa (Elsevier, 2019)
Infantile hypertrophic pyloric stenosis (IHPS) is an idiopathic disorder of infancy where the hypertrophic and enlarged pyloric muscle causes gastric obstructive symptoms of progressive emesis leading to hypochloremic, hypokalemic, metabolic alkalosis. Although this condition is ultimately treated surgically, it may present as a medical emergency due to electrolyte derangements. In the modern era, up to 88% of infants have normal electrolyte levels at presentation and very rarely do patients present with a bicarbonate >35 mmol/L. In this report, we present a unique case of a 13-week-old infant with a 9-week history of emesis who presents in hypovolemic shock with respiratory distress and the most severe electrolyte disturbances reported for an infant presenting with IHPS: base excess >30 mmol/L, sodium of 118 mmol/L, potassium of 1.6 mmol/L, chloride of 52 mmol/L and bicarbonate >50 mmol/L. Keywords: Infantile hypertrophic pyloric stenosis, Electrolyte abnormalities, Pyloromyotomy